Bacteriological load in Holstein Friesian cows with dystocia - Nechifor, Florin; Ciornei, Ștefan Gregore; Roșca, Petru (Frontiers in Veterinary Science, 2024)
The research took place on a farm in North-Eastern Romania with Holstein Friesian cows aged between 3 and 9 years. Bacteriological investigations were carried out throughout the year 2023, on a total of 35 cows, including 25 multiparous cows and 10 primiparous cows, 23 cows had eutocic parturitions and 12 cows had dystocic parturitions, during the first 3 weeks postpartum. In the case of dystocic parturition, biological samples yielded isolates including 9.3% strains classified as Staphylococcus, 8.1% strains of Escherichia coli, 4.1% strains of Arcanobacterium, and 2.3% strains of Klebsiella. Other bacterial types were identified in lesser proportions. In the case of eutocic parturition, Escherichia coli was most frequently isolated: 18.6% of the isolated bacterial strains, followed by 5.8% Pseudomonas spp., 4.6% Enterococcus spp., 4.6% Streptococcus species, 3.5% Staphylococcus spp., and Corynebacterium spp., and 2.3% Arcanobacterium spp. It is noted that on the 7th day of puerperium, the mean value of colony-forming units per milliliter (CFU/mL) was 74 × 104 CFU/mL in normal calving cows compared to 29 × 106 CFU/mL in cows with dystocia. The total number of recorded germs increases significantly during the first 14 days postpartum in all cases, higher levels being shown in cows with dystocic calving. For statistical analysis, the independent t-test (p < 0.05) was made by using the SPSS 16 software. The object of the research is the bacteriological load in Holstein Friesian cows depending on the type of eutocic parturition/dystocia.